Management of Mixed Warm/Cold Autoimmune Hemolytic Anemia: A Case Report and Review of Current Literature - Smith, Elliot C.; Kahwash, Nabeel; Piran, Siavash (Case Reports in Hematology, 2023)
Background. Mixed warm/cold autoimmune hemolytic anemia (AIHA) is a rare diagnostic entity with limited therapeutic options. Previous literature has described the diagnostic difficulty in this pathology and the limited response rates to corticosteroids. Furthermore, there is limited evidence regarding the use of rituximab in this condition. Methods. Alongside our case report, we conducted a scoping review of case reports/case series describing mixed AIHA, their treatment, and clinical outcomes since 2000. Inclusion criteria included a confirmed diagnosis of mixed AIHA (confirmed warm antibodies and cold agglutinins based on DAT). Case Summary/Results. We present a case of mixed AIHA in an 83-year-old female presenting with extensive, bilateral pulmonary embolisms and left renal vein thrombosis. The patient underwent extensive workup with no identifiable provoking etiology. Initial treatment involved prednisone therapy was transitioned to rituximab upon diagnosis of mixed AIHA. The patient demonstrated a mixed response with stable hemoglobin and transfusion independence; however, with persistently elevated hemolytic indices following completion of rituximab treatment. Our literature review identified 16 articles; two were excluded for unavailable clinical details. The most commonly associated conditions included autoimmune conditions (n = 5, 26%) and lymphoproliferative disorders (n = 3, 12%). The most common treatment involved corticosteroids; seven studies involved the use of rituximab. Conclusion. Mixed AIHA represents a complex diagnosis and optimal management is not well established. Consistent with our case, recent literature suggests a promising response to rituximab and a limited response to steroid treatment. Given the limited literature, additional studies are required to elucidate optimal management of this unique pathology.